2011
DOI: 10.1124/dmd.111.042044
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Modification of Rat Sulfotransferase 1A1 Activity in Hepatic Tissue Slices Correlates with Effects on the Purified Enzyme

Abstract: ABSTRACT:Mammalian cytosolic sulfotransferases (SULTs) catalyze the sulfation of xenobiotics as well as numerous endogenous molecules. The major aryl (phenol) SULT in rat liver, rSULT1A1, has been used extensively as a model enzyme for understanding the catalytic function of SULTs. Previous studies showed that purified rSULT1A1 displays significant catalytic changes in the presence of GSSG and other oxidants. In the present study, the effects of diamide [1,1-azobis(N,N-dimethylformamide)] and tert-butyl hydrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Previous studies with rSULT1A1 have shown that oxidative effects on the catalytic function of the purified enzyme (Marshall et al, 1997(Marshall et al, , 2000Duffel et al, 2001) are consistent with effects seen in precision cut tissue slices (Dammanahalli and Duffel, 2012). Similarities in the mechanisms of catalytic alterations seen with the two SULTs suggest that regulation by disulfide bond formation may occur within intact cells; however, the response of hSULT2A1 to disulfide bond formation within intact cells remains to be determined.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Previous studies with rSULT1A1 have shown that oxidative effects on the catalytic function of the purified enzyme (Marshall et al, 1997(Marshall et al, , 2000Duffel et al, 2001) are consistent with effects seen in precision cut tissue slices (Dammanahalli and Duffel, 2012). Similarities in the mechanisms of catalytic alterations seen with the two SULTs suggest that regulation by disulfide bond formation may occur within intact cells; however, the response of hSULT2A1 to disulfide bond formation within intact cells remains to be determined.…”
Section: Discussionmentioning
confidence: 71%
“…Although the various isoforms often have distinct, but overlapping, specificities for substrates and inhibitors, it is becoming increasingly apparent that other factors, such as the redox environment of these enzymes, can have additional effects on catalysis. For example, several family 1 SULTs are sensitive to oxidants that cause the formation of disulfide bonds (Marshall et al, 1997(Marshall et al, , 2000Duffel et al, 2001;Maiti et al, 2005Maiti et al, , 2007Liu et al, 2011;Dammanahalli and Duffel, 2012). Moreover, it is clear that, in addition to the rates of catalysis, substrate specificity may be altered by disulfide bond formation in family 1 SULTs (Marshall et al, 2000;Duffel et al, 2001;Liu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…41,55,57,6568 While most of these SULTs have been members of family 1, we have recently reported that the catalytic activity of human hydroxysteroid sulfotransferase hSULT2A1 is also sensitive to formation of disulfide bonds at key cysteine residues. 41 Alteration of the structure and function of hSULT2A1 through oxidative post-translational changes at cysteine residues led us to hypothesize that changes in catalytic function may also result from reaction of the enzyme with electrophiles that form adducts at those cysteine residues.…”
Section: Discussionmentioning
confidence: 99%
“…55 More recently, this oxidative regulation of rSULT1A1 has also been observed within intact hepatic tissue slices. 65 …”
Section: Discussionmentioning
confidence: 99%
“…28, 40 The liver slices (8 mm in diameter; 200–300 µm thick) were prepared using a Krumdieck tissue slicer (Alabama Research and Development Corporation, Munsford, AL, USA) and collected in ice-cold K-H buffer as described previously. 28, 40 …”
Section: Methodsmentioning
confidence: 99%